Analisis Perbandingan Tingkat Kesehatan Bank Pada Seabank & Bank Neo Commerce Tahun 2019-2023 - Ahmad Rifaini (CV. ITTC INDONESIA, 2025)
This study compares the financial health of Seabank and Bank Neo Commerce over the 2019–2023 period using the RGEC framework (Risk Profile, Good Corporate Governance, Earnings, Capital) in accordance with OJK and BI guidelines. Employing a quantitative comparative method, we use NPL and LDR ratios for Risk Profile; self-assessment for GCG; ROA and NIM for Earnings; and CAR for Capital.Results show that Bank Seabank maintained superior asset quality (average NPL of 0.96 %) and adequate liquidity (LDR of 84.05 %), achieved high profitability (ROA of 4.75 % and NIM of 10.41 %), and possessed very strong capital (CAR of 36.21 %), yielding a composite score of 93.33 % (PK-1: Very Healthy). In contrast, Bank Neo Commerce recorded an NPL of 1.70 % and LDR of 79.33 %, exhibited strong but more volatile NIM and lower ROA, and held a CAR of 36.45 %, resulting in a composite score of 76.66 % (PK-2: Healthy).These findings underscore Seabank’s excellence in risk management and profitability, while Neo Commerce should focus on improving asset efficiency and stabilizing ROA. Practical implications include enhancing real-time credit risk analytics, diversifying non-interest income, strengthening GCG transparency, and adopting proactive capital management and cost-efficiency strategies. This study aims to guide bank management and regulators in fostering stability and sustainable innovation in the digital banking sector.